PELATIHAN DIGITAL MARKETING, BRANDING DAN PEMASARAN ONLINE BERBASIS MARKETPLACE DAN SOSIAL MEDIA BAGI PENGEMBANGAN USAHA SAGU LICIOUS UNIT KEWIRAUSAHAAN MAHASISWA - Hafidawati Musbar; Elvi Yenie; Ida Zahrina; Vonny Setiaries Johan; Eriyati Eriyati; Bagus Duhan Irfandy; Muhammad Agung Islamy (Jurusan Teknik Lingkungan Fakultas Arsitektur Lanskap dan Teknologi Lingkungan, Universitas Trisakti, 2023)
Sago Licious is a student business at the University of Riau which is engaged in the production and marketing of processed sago-based products that was founded in 2020, this business continues to grow and has become one of the MSMEs that is slowly exploring the market in Meranti Islands Regency. However, the obstacle that is a big obstacle for business units today is weak marketing because it only focuses on meeting local needs and does not fully understand how to utilize the marketplace and social media as a capable digital marketing tool. In addition, promotion and branding patterns have not been implemented optimally. Therefore, this training is carried out as a means of increasing partners' knowledge. After the training, it is hoped that the output produced will be partners able to implement the correct marketing strategy, develop market share based on digital marketing and be able to apply branding and promotion concepts appropriately. This activity begins with a site survey and coordination with partners to identify problems. Next, a brainstorming was carried out with the PkM team to determine the solutions to be offered to partners, then an offline FGD was carried out to describe the program along with the schedule of activities to be carried out. The result of this activity was the marketing development of the Sago Licious Student Entrepreneurship Unit, the activities went well and smoothly and there were interactive discussions between resource persons and activity participants, participants also easily understood the material with clear presentation of the material and easy-to-understand training modules